Performance marketing model through acculturation innovation and market orientation in the bakery industry - Sutarlan Sulistiyani (Expert journal of marketing, 2017)
Small and Medium Enterprises (SMEs) have their own superiority in which they pervade not only in terms of human resources, but also in their role in national economic development. The aim of this study is to develop acculturation innovation and competing superiority for increasing the marketing development of the bakery business actors in Central Java. This studys sample consists of 161 respondents who are bakery business owners from Central Java. By using the purposive sampling technique, several criteria were considered for the SMEs representatives from the bakery industry sample, such as the SMEs must be certified at Disperindag, have at least one employee, and invest at least IDR 1.000.000,- . The analyzing method that is used in this study is SEM. The result of the study shows the market orientation with specific dimensions, such as gaining information about the customers needs, competitors powers, and functions coordination affected competitors superiority, and acculturation innovation. While it comes to some dimensions such as changes in culture-based products, culture-based price changing, culture-based packaging, and production processes, competing superiority is affected.
2758454-9; 2344-6773; Expert journal of marketing; 778946770